Butanol as a co-solvent for transesterification of rapeseed oil by methanol under homogeneous and heterogeneous catalyst - Hájek, Martin; Vávra, Aleš; Mück, Jáchym (Elsevier Science, 2020)
The paper focuses on the use of methanol (M) together with butanol (B) in transesterification of rapeseed oil (O) under homogeneous (KOH) and heterogeneous catalysis (Mg-Fe mixed oxides with molar ratio of magnesium to iron of 2.9). The novelty lies in the use of these types of alcohols together under various reaction conditions and the determination of ternary plots for the reaction components. The advantage of using butanol consists of the formation of a homogenous reaction mixture and the slightly higher caloric value of the formed esters. For the homogeneous catalyst, the influences of the (i) molar ratios of reaction components, (ii) temperature, (iii) amount of catalyst and (iv) method of stopping the transesterification were studied in the course of transesterification. The properties of the ester and glycerol phases were determined, including ester loss in the glycerol phase. The ester yield was 97% after 10 min of reaction for 60 degrees C, and the O:M:B ratio was 1:6:2, representing a significant decrease in time compared with methanol only (90 min). However, the content of potassium ions was higher because butyl ester results in higher solubility of potassium ions. For the heterogeneous catalyst, the synthesized materials were characterized by the chosen method and tested in transesterification with methanol, butanol and their combination. The addition butanol caused the higher yield than only for methanol or butanol only.
Butanol jako kosolvent pro transesterifikaci řepkového oleje pomocí metanolu během homogenní a heterogenní katalýzy
Keywords: transesterification; biodiesel; esters; butanol; methanol; transesterifikace; bionafta; estery; butanol; metanol